Beyond the visible: revealing the creative power of the Cape enslaved and the empowering influence of Sufi inspired Islam - Hendricks, Redawaan (My University, 2021)
This dissertation will contextualise Sufi Islam and its centrality in the process that the Cape enslaved embarked upon to ensure their independent development since the first enslaved people arrived on the shores of Cape Town until slavery was abolished in 1838 and towards the end on the century. A theoretical framework of power will be utelised to appraise slave agency which has been driven by Sufi infused Islam, that laid the foundations for change and enabled the gaps in community life to be enriched by Muslim common religious Sūfi practices. Many of the enslaved people resisted acceptance of the prevailing slave master’s religion of Christianity and instead opted to embrace Islam. The form of Islam that evolved at the Cape was a particular type of Islam which was strongly influenced by Sufism. This reality is a subtle, yet powerful, way in which the Cape enslaved resisted the hegemonic forces of the slave masters in particular and the colonial authority in a broader sense. The dissertation will set about to explore the communal, social and cultural spaces which opened up for the enslaved to develop a sense of self and community...
A dissertation submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirement for the Master of Arts in Heritage, 2021